Exploring Public Satisfaction in Rural Public Services: 2022 Case Study: Penelusuran Kepuasan Masyarakat pada Layanan Publik Pedesaan: Studi Kasus Tahun 2022 - Viola, Famela Octa; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2023)
This study investigates public satisfaction with service provision in Desa Larangan, Kecamatan Candi, Kabupaten Sidoarjo, focusing on nine key elements outlined in the Ministry of Administrative and Bureaucratic Reform's guidelines. Evaluating citizen satisfaction in areas ranging from requirements to infrastructure, the research surveys Organisasi Perangkat Daerah (OPD) and the Village Government as service recipients. Findings reveal an overall favorable assessment, showcasing a commendable service quality and performance with a Satisfaction Index of 79.02. Notably, infrastructure facilities garnered the highest average score (3.28), while requirements scored the lowest (3.02). This study highlights the positive quality of rural public service provision and underscores areas for potential enhancement, serving as a benchmark for governance optimization. Highlights: Comprehensive Assessment: Evaluated nine dimensions of service satisfaction. Favorable Findings: Overall positive performance with notable room for improvement. Governance Benchmark: Offers insights for optimizing rural service delivery. Keywords: Public Satisfaction, Service Quality, Rural Governance, Citizen Feedback, Administrative Performance